DEIXIS AND SOCIAL RELATIONS IN SURAH YUSUF: A PRAGMATIC APPROACH AND CRITICAL DISCOURSE ANALYSIS: DEIKSIS DAN RELASI SOSIAL DALAM SURAH YUSUF: PENDEKATAN PRAGMATIK DAN ANALISIS WACANA KRITIS - Istajib, Istajib; Ishlah, Fauzi (Journal of Arabic Language and Literature (ALLAIS), 2025)
In Qur’anic linguistic studies, pragmatic aspects such as deixis are often overlooked in favor of phonological or syntactic features, despite their vital role in shaping meaning and divine messages. This study is a descriptive qualitative research that aims to analyze the use of personal, temporal, and spatial deixis in Surah Yusuf. The approach employed is pragmatic, drawing on Levinson’s theory of deixis, combined with Fairclough’s model of critical discourse analysis. Data were collected through documentation of the text of Surah Yusuf in the Qur’anic manuscript. The data analysis technique involved qualitative interpretation by identifying and categorizing types of deixis and uncovering the social and ideological meanings behind their use. The findings reveal that deixis in divine revelation is not merely linguistic but functions as a tool for constructing identity, social legitimacy, and spiritual transformation. Personal deixis reflects shifts in status and power relations; temporal deixis shapes the narrative chronology; and spatial deixis emphasizes the significance of movement and alienation. Thus, Surah Yusuf demonstrates how revelation conveys divine messages through linguistically and socially meaningful structures.